2021
DOI: 10.3390/cancers13153716
|View full text |Cite
|
Sign up to set email alerts
|

Primary Aldosteronism: Metabolic Reprogramming and the Pathogenesis of Aldosterone-Producing Adenomas

Abstract: Aldosterone-producing adenomas (APAs) are characterized by aldosterone hypersecretion and deregulated adrenocortical cell growth. Increased energy consumption required to maintain cellular tumorigenic properties triggers metabolic alterations that shape the tumor microenvironment to acquire necessary nutrients, yet our knowledge of this adaptation in APAs is limited. Here, we investigated adrenocortical cell-intrinsic metabolism and the tumor immune microenvironment of APAs and their potential roles in mediati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…In a recent study, transcriptome data analysis identified alterations in transcriptome signatures in pathways related to mitochondrial fatty acid β-oxidation and peroxisome proliferator receptor-α ( PPARα ), with suppression of ferroptosis suppressor genes and overexpression of genes related to glycolysis/glyconeogenesis in APAs. Furthermore, KCNJ5 mutated APAs that have a higher proliferative index display increased expression of genes involved in glycolysis and lipid metabolism, an observation reminiscent of the well-characterized role of metabolic reprogramming in cancer progression [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, transcriptome data analysis identified alterations in transcriptome signatures in pathways related to mitochondrial fatty acid β-oxidation and peroxisome proliferator receptor-α ( PPARα ), with suppression of ferroptosis suppressor genes and overexpression of genes related to glycolysis/glyconeogenesis in APAs. Furthermore, KCNJ5 mutated APAs that have a higher proliferative index display increased expression of genes involved in glycolysis and lipid metabolism, an observation reminiscent of the well-characterized role of metabolic reprogramming in cancer progression [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, adrenocortical tumor cells appeared to possess mechanisms for counteracting metabolic stress through upregulation of antioxidant systems. APAs were documented to display a high proportion of tumor cells, suggesting that their particular transcriptome profile enables them to escape from immune surveillance [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Somatic mutations of KCNJ5, ATP1A1, ATP2B3, CACNA1D, CACNA1H, CLCN2, or CTNNB1 genes that drive autonomous aldosterone production have been documented in APAs [5][6][7][8][9][10][11][12][13]. Recently, Gong, et al, suggested that metabolic reprograming involved with tumorigenesis in KCNJ5 mutant APA [14]. However, the molecular mechanisms of genesis or growth of APAs mediated by ATP1A1 mutations have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular features of a novel mutation in the ATP2B3 gene are presented in detail in the article by Liao et al [ 2 ]. By using advanced bioinformatics approaches, Gong et al characterized the metabolome and tissue microenvironment in aldosterone-producing adenomas and showed metabolic reprogramming toward fatty acid β-oxidation and glycolysis; moreover, an immunosuppressive tissue microenvironment was also found [ 3 ]. In a systematic review, Spyroglou et al present recent developments in the transcriptomics, epigenetics and metabolomics of primary aldosteronism [ 4 ].…”
mentioning
confidence: 99%